2021
DOI: 10.3390/app11062677
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Student Learning in Learning Management Systems: An Application of Educational Data Mining Techniques

Abstract: In this study, we used a module for monitoring and detecting students at risk of dropping out. We worked with a sample of 49 third-year students in a Health Science degree during a lockdown caused by COVID-19. Three follow-ups were carried out over a semester: an initial one, an intermediate one and a final one with the UBUMonitor tool. This tool is a desktop application executed on the client, implemented with Java, and with a graphic interface developed in JavaFX. The application connects to the selected Moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 42 publications
2
41
0
4
Order By: Relevance
“…it has been found that the behavioural profiles within each collaborative group, that are represented in Heat Map, do not have a homogeneous pattern of interaction between the members of each collaborative group and that there are always one or two members in each group who set the pace of work (Dobashi et al, 2019;Sáiz-Manzanares et al, 2020b). Therefore, it can be concluded that monitoring the learning process in each student is essential throughout the entire development for the detection of students at risk, especially in the initial and intermediate phases of the learning process (Bannert et al, 2014;Bogarín et al, 2018;Cerezo et al, 2016;Sáiz-Manzanares et al, 2021b). Ideally, an initial measurement should be taken two weeks into the course, an intermediate measurement (in the middle of the course) and a final measurement (one or two weeks before the end of the course).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it has been found that the behavioural profiles within each collaborative group, that are represented in Heat Map, do not have a homogeneous pattern of interaction between the members of each collaborative group and that there are always one or two members in each group who set the pace of work (Dobashi et al, 2019;Sáiz-Manzanares et al, 2020b). Therefore, it can be concluded that monitoring the learning process in each student is essential throughout the entire development for the detection of students at risk, especially in the initial and intermediate phases of the learning process (Bannert et al, 2014;Bogarín et al, 2018;Cerezo et al, 2016;Sáiz-Manzanares et al, 2021b). Ideally, an initial measurement should be taken two weeks into the course, an intermediate measurement (in the middle of the course) and a final measurement (one or two weeks before the end of the course).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Park & Jo, 2017 ) have found significant differences in learning outcomes according to the teachers’ teaching style and the learning style of students (Sáiz-Manzanares et al, 2021a ). Another relevant aspect facilitated by LMSs is the early detection of at-risk students, Strang ( 2016 ) analyses the relationship between the use of LMSs and students' learning patterns on the platform (Sáiz-Manzanares et al, 2021b ). In this line, regression analysis techniques, among others, make it possible to detect successful and risky behavioural patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring their learning and enables the application of personalized actions for each individual student according to their profile. A software has been recently patented to monitor student learning in the Moodle platform [27].…”
Section: Learning Strategies and Student Profilesmentioning
confidence: 99%
“…Para lograrlo deben incluir, entre otros: a) un análisis de los conceptos previos del alumnado con el fin de diseñar distintos niveles de dificultad; b) tareas de aprendizaje que incluyan un diseño de aprendizaje por descubrimiento; y c) retroalimentación orientada a procesos para que el aprendiz pueda aprender del error. Todas estas funcionalidades potenciarán un aprendizaje personalizado acorde con el ritmo de aprendizaje de cada estudiante (Sáiz-Manzanares et al, 2021, Sáiz-Manzanares et al, 2019bVázquez-Dorrío, 2016;Vázquez-Dorrío & Vázquez-Dorrío, 2018).…”
Section: Ecología De Aprendizaje Autorreguladounclassified
“…En estos contextos combinados en los que se promovió el aprendizaje autorregulado del alumnado, este presentó un aumento significativo en los procesos de autorregulación del aprendizaje y percibieron un mayor apoyo por parte del profesorado (Martínez-Sarmiento & González, 2019). Del mismo modo, en experiencias de aprendizaje autorregulado realizadas durante el confinamiento, el seguimiento del alumnado y la intervención personalizada dio lugar a bajas tasas de abandono y alta satisfacción del alumnado con el proceso de enseñanza-aprendizaje (Sáiz-Manzanares et al, 2021).…”
Section: Introductionunclassified